LITERATURE AND MUSIC: CO-OPERATION, RECEPTION - Oleksiuk, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
There is the guestion in the article about synthesis of imaginative literature and musical images, about facilities of their perception in present sociocultural space, about actualization of methods of education of writing and music works. It is proved that reception of cultural wealth, except for artistic, comes forward the original constituent of the integral system of creation the image: co-operation of literature and music its art mastering,